Transarterial‐ chemoembolization remains an effective therapy for intermediate‐stage hepatocellular carcinoma with preserved liver function. Issue 10 (14th August 2020) - Saito, Natsuhiko; Tanaka, Toshihiro; Nishiohuku, Hideyuki; Sato, Takeshi; Masada, Tetsuya; Matsumoto, Takeshi; Anai, Hiroshi; Sakaguchi, Hiroshi; Sueyoshi, Satoru; Marugami, Nagaaki; Kichikawa, Kimihiko
Abstract : Aim: To evaluate outcomes as well as prognostic factors of transarterial chemoembolization (TACE) in intermediate‐stage hepatocellular carcinoma (HCC) with preserved liver function to determine positioning of TACE. Methods: Of 158 treatment‐naïve patients with intermediate‐stage HCC who received initial TACE from February 2007 to January 2016, 113 patients met the following inclusion criteria: no combined therapy within 4 weeks after initial TACE, and Child–Pugh score under 7. Response rate and overall survival were evaluated. The prognostic factors were investigated in univariate and multivariate analyses using Cox proportional hazards models. The deterioration of liver function after repeated TACE was also evaluated. Results: The response rate was 92.7% (complete response, 63.3%; partial response, 29.4%). The median survival time was 45.2 months. Survival rates at 1, 2, and 3 years were 90.4%, 77.0%, and 60.8% respectively. Age ≥ 75 years ( P  = 0.022), serum α‐fetoprotein level ≥ 200 ng/mL ( P  = .010), tumor number ≥ 11 ( P  = 0.008), and heterogeneous enhancement on dynamic computed tomography ( P  = 0.024) were poor prognostic factors. The deterioration rate of Child–Pugh score and albumin–bilirubin grade was 18.5% and 12.3%, respectively, after the first TACE, 15.6% and 5.1%, respectively, after the second TACE, and 14.5% and 11.1%, respectively, after the third TACE. Conclusion: Superselective TACE can achieve high tumor response rates with prolonged overall survival for patients with intermediate‐stage HCC with preserved liver function. Age, serum α‐fetoprotein level, tumor number ≥ 11, and heterogeneous enhancement on dynamic computed tomography indicated significantly poor prognosis.